"What an Eccentric Performance": Storytelling in Online Let's Plays. Issue 3 (May 2019) - Kerttula, Tero
In this article, I examine the phenomenon called Let's Play (LP) and conduct a narrative analysis on two LPs made of Sierra Entertainment's Phantasmagoria games. The LPs tell viewers a story different from the one told in the games, that is, they tell the story of the player rather than that of the game. In that story, the experience of playing a video game is revealed to the audience. This story would be hidden without the player-narrators know as LPs around the world. I conduct my analysis by describing seven different narrative elements that form the narration of a LP and explain how these elements together form this story of the player.